Comb-shaped polymer grafted with REDV peptide, PEG and PEI as targeting gene carrier for selective transfection of human endothelial cells. Issue 7 (30th January 2017) - Wang, Haixia; Li, Qian; Yang, Jing; Guo, Jintang; Ren, Xiangkui; Feng, Yakai; Zhang, Wencheng
Abstract : Several REDV peptide molecules are covalently linked onto an amphiphilic block copolymer to obtain REDV-modified polycationic polymer as a gene carrier with targeting function. The targeting gene complexes show high cell recognition and binding affinity to human endothelial cells. Abstract : If plasmid complexes prepared from targeting carriers have endothelial cell selectivity and high transfection efficiency, they can specifically enhance rapid endothelialization by delivering the corresponding gene plasmids. A high content of functional groups in the carriers benefits high selectivity efficiency. Herein, we have synthesized a comb-shaped polymer bearing several Arg-Glu-Asp-Val (REDV) peptides and poly(ethylene glycol) as a pEGFP-ZNF580 gene carrier with cell-type recognition of human endothelial cells. An amphiphilic block copolymer of poly(2-hydroxyethyl methacrylate)- block -poly(ε-caprolactone)- graft -poly(ethylene glycol)- graft -poly(ethyleneimine) conjugated with REDV peptide (PHEMA- b -PCL- g -PEG- g -PEI-REDV) is synthesized, and nanoparticles of it are prepared by polymer self-assembly. This polycationic PHEMA- b -PCL- g -PEG- g -PEI-REDV carrier effectively condenses pEGFP-ZNF580 plasmid to form REDV-targeted complexes and protects pEGFP-ZNF580 integrity from enzymatic hydrolysis. These REDV-targeted complexes exhibit low cytotoxicity but high transfection efficiency to EA.hy926 cells compared with non-targeted complexes (PHEMA- b -PCL- g -PEG- g -PEI/pEGFP-ZNF580) as demonstrated by MTT assay, fluorescence-activated cell sorting analysis and fluorescence analysis. Furthermore, the relative protein level of endothelial cells transfected by REDV-targeted complexes is higher than that by non-targeted complexes. Therefore, REDV-bearing carriers may have potential as effective and targeting transfer carriers for pEGFP-ZNF580 plasmid, and their complexes can be used in the endothelialization of artificial vascular grafts.